Comparative transcriptome analysis of molecular mechanisms underlying adventitious root developments in Huangshan Bitter tea (Camellia gymnogyna Chang) under red light quality - Fu, Hao; Wei, Xu; Chen, Qian; Yong, Shunyuan; Liu, Qinjin; Dang, Jiangbo; Wu, Di; Liang, Guolu; Guo, Qigao (Frontiers in Plant Science, 2023)
As the formation of adventitious roots (AR) is an important part of regeneration in vitro of tea plants, the lower rooting rate of Huangshan Bitter tea (Camellia gymnogyna Chang) cuttings has been limiting its propagation and preservation. Light as a crucial environmental factor influences AR formation. However, the role of red light in tea plants remains unclear. In this study, Huangshan Bitter tea was induced by white light (control, WL) and red light (660 nm, RL) qualities 36 days after induced treatment (DAI) to investigate dynamic AR formation and development, anatomical observation, hormones content change, and weighted gene co-expression network analysis (WGCNA) of the transcriptome. Results showed that RL promoted the rooting rate and root characteristics compared with WL. Anatomical observations displayed that root primordium was induced earlier by RL at the 4 DAI. RL positively affected IAA, ZT and GA3 content and negatively influenced ABA from the 4 to 16 DAI. The results of the RNA-seq and analysis of differential expression genes (DEGs) exhibited extensive variation in gene expression profiles between RL and WL. Meanwhile, the results of WGCNA and correlation analysis identified 3 highly correlated modules and hub genes mainly participated in 'response to hormone', 'cellular glucan metabolic progress', and 'response to auxin'. Furthermore, the proportion of ethylene response factor (ERF), myeloblastosis (MYB), basic helix-loop-helix (bHLH), and WRKYGQK (WRKY) were the top four of total transcription factors (TFs) in DEGs. Our results indicated that the AR-motivating potential of red light was the result of complex hormone interactions in tea plants by regulating the expression of related genes, which was an important reference to shorten breeding cycles and accelerate superiority.